Problem : Calculate the derivative of the function $f: ]0,+\infty\left[\longrightarrow \mathbb{R}\right.$ defined by $f(x)=x^{n-1} \ln x$.

Solution Let $g_{1}(x)=x^{n-1}$ et $g_{2}(x)=\ln x .$ So we have$f=g_{1} g_{2}$ for all $k$ verifying $1 \leq k \leq n-1$ we have $$ g_{1}^{(k)}(x)=(n-1) \cdots(n-1-k+1) x^{n-1-k} $$ et $$ g_{1}^{(n)}(x)=0 $$ The Leibniz formula gives

$\begin{array}{c} f^{(n)}(x)=\sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right) g_{1}^{(k)}(x) g_{2}^{(n-k)}(x) \\ =x^{n-1} \frac{(-1)^{n-1}(n-1) !}{x^{n}}+\sum_{k=1}^{n-1}\left(\begin{array}{l} n \\ k \end{array}\right)(n-1) \cdots(n-1-k+1) x^{n-1-k} \frac{(-1)^{n-k-1}(n-k-1) !}{x^{n-k}} \\ =\frac{(-1)^{n-1}(n-1) !}{x}+\sum_{k=1}^{n-1}\left(\begin{array}{l} n \\ k \end{array}\right) \frac{(-1)^{n-k-1}(n-1) !}{x}\\ =-\frac{(n-1) !}{x} \cdot \sum_{k=0}^{n-1}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k} \end{array}$

The sum above is the same as $\sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k}$ (prived of $k=n,$) which is equal to -1

We obtain $$ f^{(n)}(x)=\frac{(n-1) !}{x} $$

What I don't get: What's the point of this step:

we have $$ g_{1}^{(k)}(x)=(n-1) \cdots(n-1-k+1) x^{n-1-k} $$ et $$ g_{1}^{(n)}(x)=0 $$

and which solution is wrong?

I spent a lot of time already on this, I think it's a matter of indices I can't point, both solutions seem correct to me.

How I calculated :

we have that

$\ln ^{(n)}(x)=\frac{(-1)^{n-1}(n-1) !}{x^{n}}$


$(x^{n-1})^{(k)} = \frac{(n-1) !x^{n-1-k}}{(n-1-k) ! }$

\begin{aligned} f^{(n)} &=\sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)\left(x^{n-1}\right)^{(k)}(\ln x)^{(n-k)} \\ &=\sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right) \frac{(n-1) !x^{n-1-k}}{(n-1-k) ! } \frac{(n-1-k) !(-1)^{n-1-k}}{x^{n-k}} \\ =& x^{-1} \sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(n-1) !(-1)^{n-k-1} \end{aligned}

$= (-1)x^{-1} (n-1) ! \sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k}$

which should give me zero? since

$\sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k} = (1+(-1))^{n}=0 $


I know I'm not answering the question, but I can't resist the temptation to show you a trick to arrive at the solution faster (no Leibniz formula): Integrate once before differentiating.

Let $f_n(x)=x^{n-1}\ln x$. Compute one of its primitives (antiderivatives) by integrating by parts: $$\int_0^xf_n(t)dt=\frac{x^n}n \ln x-\frac{x^{n-1}}{n^2}=\frac{f_{n+1}(x)}n-\frac{x^{n-1}}{n^2}$$ So to obtain $f_n^{(n)}(x)$, we just need to differentiate the above $n+1$ times (noting that this will cancel the second term as it's a polynomial of degree $n-1$): $$f_n^{(n)}(x)=\frac{f_{n+1}^{(n+1)}(x)}n$$ Solving this recurrence formula gives you the result $$f_n^{(n)}(x)=(n-1)!f_1^\prime(x)=\frac{(n-1)!}{x}$$


Your solution is almost correct (and neither $g_1^{(k)}(x)$ or $g_1^{(n)}(x)$ are wrong). The only problem is that $(x^{n-1})^{(k)} = \frac{(n-1) !x^{n-1-k}}{(n-1-k) ! }$ is only true for $0 \le k \le n-1$. For $k \ge n$, the $k$th derivative will be $0$. For example, the $2$nd derivative of $x^1$ is $0$.

The step $$f^{(n)} =\sum_{k=0}^{n}\binom{n}{k}\left(x^{n-1}\right)^{(k)}(\ln x)^{(n-k)} \tag 1$$

is right. But then at the next step, the sum should only go from $k = 0$ to $k = n-1$ since $\left(x^{n-1}\right)^{(n)} = 0$.

Then after that, the same logic applies, so you would end up with $$= (-1)x^{-1} (n-1) ! \sum_{k=0}^{n-1}\binom{n}{k}(-1)^{n-k} = \frac{(n-1)!}{x}$$

  • $\begingroup$ When you say, "But then at the next step, the sum should only go from $k = 0$ to $k = n-1$ since $\left(x^{n-1}\right)^{(n)} = 0$" how so, and why? $\endgroup$
    – squareroot
    Dec 16 '20 at 19:25
  • $\begingroup$ @squareroot Maybe a better explanation would have been splitting it from $k = 0$ to $k = n-1$ and having a separate case for $k = n$. When $k = n$, the summand would be $0$ since $\left(x^{n-1}\right)^{(n)} = 0$, so the $k = n$ term can be "chopped off". $\endgroup$ Dec 16 '20 at 19:55
  • $\begingroup$ How does not separating the $k=n$ makes the following wrong $ (-1)x^{-1} (n-1) ! \sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k} = (-1)x^{-1} (n-1) ! \sum_{k=0}^{n}\left(\begin{array}{l} n \\ k \end{array}\right)(-1)^{n-k} = (-1)x^{-1} (n-1) ! (1+(-1))^{n}=0$ $\endgroup$
    – squareroot
    Dec 19 '20 at 20:16
  • $\begingroup$ @squareroot That's all right, but the steps taken to get to that first point are wrong. To start off, the sum should only be from $k = 0$ to $k = n-1$. $\endgroup$ Dec 19 '20 at 20:35
  • $\begingroup$ why does the sum should only be from $k=0$ to $k=n-1$ just because the nth term is null? what in the steps is exactly wrong or doesn't suffice any necessary condition ? $\endgroup$
    – squareroot
    Dec 19 '20 at 20:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.